Hyve-3D and the 3D Cursor: Architectural co-design with freedom in Virtual Reality. (June 2016) - Dorta, Tomás; Kinayoglu, Gokce; Hoffmann, Michael
Hybrid Virtual Environment 3D (Hyve-3D) is a system that allows architectural co-design inside Virtual Reality by a new model of interaction through a 3D cursor. It augments the concept of the cursor to better interact with three-dimensional virtual spaces, rethinking it as a drawing/control plane and viewpoints inside the virtual world. Handheld tablets intuitively manipulate 3D cursors. Users can simultaneously access their individual complementary views on the tablets as personal windows into the shared immersive display. They can concurrently sketch in three dimensions, transform, and manipulate three-dimensional objects using the tablets as tangible props and collectively navigate the scene using the tablet as a 3D trackpad. The system implementation and co-design assessments of different settings are presented.